Developing a mold technology module for freescale – study on effects of materials (compound properties) and molding process parameters on package moldability for QFP - Tan Hui Khin (Universiti Malaysia Perlis, 2008)
In integrated circuit (IC) Packaging, there are several processes involved. The main processes for leaded package are wafer mount, wafer saw, die attach, wire bonding, molding, plating, singulation, trim and form. Molding (encapsulation process) is one of the key process which is done in order to protect an electronic device from moisture, ion contamination, radiation, interference, and harsh environment. This means the package provides protection for the IC and defines the shape of the outer surface of the package. By applying pressure, the heated molten molding compound (EMC) is transferred from a plunger, through the runners, and into the mold cavities. There are many variables in terms of materials (EMC), equipments and tooling, and process parameters that should be controlled and improved in order to get a reliable and moldable product. In this research, the Side Gate Molding (SGM) technique was used for molding the 20mm x 20mm LQFP 144 Lead. This study is divided into two parts which are: (i). EMC Study; (ii). SGM Parameters Study. For the EMC study, the moldability of Green and Non-Green EMC are studied and compared to determined which type of EMC show a better moldability performance. From the result, it showed that both green and non-green EMC had an acceptable moldability performance. However, green EMC is more preferable in electronic packaging industry due to the safety consideration and better moldability in wire sweep issue. However, for SGM parameters study, a Design of Experiment (DOE) was conducted to generate the parameters range for better moldability which depends on which defects are more favorable to eliminate or reduce from a process parameters windowing.